Sociocultural Ideal Internalization, Body Dissatisfaction and Weight Control Behavior among Adolescent Athletes and Non-Athlete Adolescents. Does that Need Education? - Simona Pajaujienė; Rasa Jankauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Many young people are concerned about their body size and shape because of the social pressures to conform to a thin body ideal. Athletes face additional pressures related to performance and, for some of them, aesthetic and weight category demands. Modification of body build is often attempted via diet and exercise, so the data were also gathered on attitudes toward eating and weight control - exercising behavior. Research aim was to examine media influence, body dissatisfaction, unhealthy weight loss behavior (UWLB) and unhealthy exercising behavior (UEB), risk of eating disorders (DE) in the sample of non-athletic and athletic adolescents. We proposed a hypothesis that adolescents aiming at matching social expectations of body image were more likely to be dissatisfied with their appearance as well as have worse weight control behavior and higher risk of eating disorders. We  expected that these associations would not differ among athletic and non-athletic adolescents.   Research methods. 11th grade students (n = 805, mean age - 17.23 (0.6) years, 476 (58.9%) females, 233 (28.9%) athletes) filled in anonymous questionnaires, which consisted of Sociocultural Attitudes Towards Appearance Scale (SATAQ-3, Thompson et al., 2004), Body Areas Satisfaction Scale from MBSRQ-AS (Cash, 2004), EAT-26 (Garner et al., 1982) and specially for this study created Unhealthy Weight Loss Behavior Scale. Research results. Nearly half of adolescents reported using at least one UWLB or/and UEB, 87 adolescents (more girls, p < 0.05) full into ED risk group with no differences between athletes and non-athletes (p > 0.05). Media influence did not differ between groups, but non-athletes were more dissatisfied with their body (p  < 0.05), had more expressed UWLB (p < 0.05), although adolescents who participated in sports demonstrated more UEB (p < 0.05). Discussion and conclusions. Adolescents  who more dramatically internalized the social body standards were more dissatisfied with their appearance, had worse weight control behavior and higher risk for eating disorder. These associations basically did not differ between athletes and non-athletes. Keywords: body dissatisfaction, weight control, adolescence, athletic activities.